Narrative based information: is it the facts or their packaging that matters? - Shaun P. Hargreaves Heap; Aikaterini Karadimitropoulou; Eugenio Levi (Masaryk University, Faculty of Economics and Administration, 2021)
People typically do not acquire new information about the facts of the economy through consulting official statistics; they read or listen to mediatype reports/stories on the economy where the facts are packaged in a story. This paper tests with an experiment whether the explanatory style used in such media-type stories affects individual decision making. We also compare this particular narrative influence with that of the actual facts contained in the story. Our subjects receive a media-type story about the economy before they play a minimum effort game. The media story has either good or bad background facts about the economy and we use the psychological theory of explanatory styles to present these facts in a narrative style designed to engender either optimism or pessimism. We find evidence that the explanatory style matters more than facts in the sense that optimistic styles support higher equilibria than pessimistic ones while the influence of the facts itself is weaker.
Keywords: E71; 330; narratives; information; media; minimum effort game